Maupertuis - Beeson, D (Voltaire Foundation, 2017)
This intellectual biography stands as the definitive account of Maupertuis’s career. His much-publicised quarrel with Voltaire – which ultimately destroyed him – has cast a long shadow over his reputation. Maupertuis’s true contribution to eighteenth-century scientific debate re-emerges clearly in this important reassessment. Acknowledgements Introduction: Why Maupertuis? Chronology of Maupertuis’ life 1. The scientific background The triumph and decline of Cartesianism Natural history and the attack on dualism Developments in physics: point-mass mechanics Theories of gravitation Natural history: ovism and spermatism – ontological and teleological reasoning Ontology and teleology in physics: the case of optics Empiricism and rationalism: the shape of the Earth 2. The years of apprenticeship: 1698-1732 Saint-Malo and Paris London Vis viva: the debate reopens Basle and Paris Hesitations over Leibnizianism Montpellier: an interlude for natural history On the shapes of celestial bodies De figuris Genesis of the Figures des astres 3. The shape of the Earth: 1732-1740 France’s first Newtonian Reactions to the Figures des astres The shape of the Earth: the debate reopens Factions in the Academy: the generation gap Counter-attack: the search for a decisive test After Lapland A new offensive: Examen désintéressé Twisting the knife Elémens de géographie Lettre d’un horloger anglois 4. From Paris to Berlin: 1740-1745 Prussia and the Berlin Academy of Sciences Maupertuis and Frederick Maupertuis in Paris Launching the Berlin Academy Closing a chapter Speculative philosophy Thoughts on science: address to the Académie française Towards least-action principle: work on statics From statics to optics Natural history A thinker in transition 5. The years of triumph: 1746-1751 Berlin before the Koenig affair La Mettrie: moral philosophy La Mettrie: natural history Leonhard Euler Guillame The peaks of achievement 6. Decline and death: 1751-1759 Maupertuis and Koenig Revisions to existing texts Replies to critics New work Maupertuis’s last journey Conclusion: an attempt at an assessment Appendix: Maupertuis’ mathematical analysis of point-mass collisions Bibliography Index